Democracy as a Goal of Union Organization : An Interpretation of the United States Experience - Muthuchidambaram, S. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1969)
This paper presents a overall review and an interpretation of the vast existing literature on union democracy in the United States.